Transition to just in time inventory - Huberty, Daniel P. (University of Wisconsin--Stout, 2018)
SWS, a division of AB International is a company that designs, builds and installs over the top merchandising displays. SWS had inventory control issues within their countertop department and also racking shortages throughout their warehouse. SWS was receiving their order forms from Party City stores the week of shipment. This meant that SWS needed to carry bulk quantities of all countertop sizes and styles. To eliminate this, SWS transitioned to a just-in-time inventory strategy. To achieve this, they requested all order forms and floor plans to be sent to them three months prior to the ship date. This allowed SWS to order only the sizes and styles that we going to be used in upcoming stores. By making this transition it also freed up the necessary racking space that SWS needed for other displays.
Keywords: Just-in-time systems; Countertops industry; Inventory control